Modelagem termodinâmica de uma usina híbrida concentradora solar (CSP)-biomassa no semiárido da Paraíba - Costa Neto, Luiz Bonfim Vieira (2020)
The necessity of diversification of the Brazilian energy matrix, associated with the worldwide appeal for mitigation of polluting sources and the consequent environment preservation, make the renewable energy sources an interesting alternative, considering the amount of natural resources that the country has. Despite the great Brazilian solar potential, this source represents only 1.35% of the installed energy in Brazil currently, being in its entirety, photovoltaic plants. Concentrated solar power plants have a large advantage over other renewable sources of energy, due to the possibility of thermal storage, which allows generation of eletricity at times of low or no solar radiation incidence, thus having a higher efficiency, capacity factor and reliability. The use of biomass for power generation is a more widespread technology in Brazil, mainly due to the cogeneration systems of sugar-alcohol industries, representing 8,46% of the installed energy power in Brazil. The present work aims to accomplish a thermodynamic modelling of an hybrid concentrating solar power (CSP)-biomass power plant, with project power of 50MWe, parabolic trough collector and thermal energy storage, to be installed in the semiarid region of Paraíba state, making a comparasion between a plant with superheating and reheating carried out through direct combustion of biomass, with a plant that uses biomass only as an energy source for the backup system. Such modification in the plant structure promoted a 4.05% efficiency gain in the power cycle, as well as a 48.1% reduction in the required collecting surface area, and a 34.7% reduction in the amount of salt. required for the thermal storage system.